Melanoma in women of childbearing age and in pregnancy in California, 1994–2015: a population‐based cohort study. (23rd August 2022) - Kiuru, M.; Li, Q.; Zhu, G.; Terrell, J.R.; Beroukhim, K.; Maverakis, E.; Keegan, T.H.M.
Abstract: Background: Melanoma is one of the most common malignancies during pregnancy. There is debate regarding the impact of pregnancy on the prognosis of melanoma. Recent large population‐based studies from the United States are lacking. Objectives: To determine the characteristics and survival of women with pregnancy‐associated melanoma. Methods: This population‐based, retrospective cohort study used California Cancer Registry data linked with state‐wide hospitalization and ambulatory surgery data to identify 15–44‐year‐old female patients diagnosed with melanoma in 1994–2015, including pregnant patients. Multivariable logistic regression compared demographic and clinical characteristics between pregnant and non‐pregnant women with melanoma. Multivariable cox proportional hazards regression models assessed melanoma‐specific and overall survival. Results: We identified 13 108 patients, of which 1406 were pregnant. Pregnancy‐associated melanoma was more frequent in Hispanic compared to non‐Hispanic White women. Melanoma occurring post‐partum was associated with greater tumour thickness (2.01–4.00 vs. 0.01–1.00 mm, odds ratio 1.75, 95% confidence interval: 1.03–2.98). There were otherwise no significant differences between pregnant and non‐pregnant women. Worse survival was associated with Asian, Black and Native American race/ethnicity (vs. non‐Hispanic White), lower neighbourhood socio‐economic status, public insurance, tumour site, greater tumour thickness and lymph node involvement, but not pregnancy. Conclusions: Melanoma occurring post‐partum was associated with greater tumour thickness, but pregnancy status did not affect survival after melanoma. Race/ethnicity, socio‐economic status and health insurance impacted survival, emphasizing the importance of reducing health disparities.